2010
DOI: 10.1073/pnas.0909616107
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function, and self-assembly of single network gyroid ( I 4 1 32) photonic crystals in butterfly wing scales

Abstract: Complex three-dimensional biophotonic nanostructures produce the vivid structural colors of many butterfly wing scales, but their exact nanoscale organization is uncertain. We used small angle X-ray scattering (SAXS) on single scales to characterize the 3D photonic nanostructures of five butterfly species from two families (Papilionidae, Lycaenidae). We identify these chitin and air nanostructures as single network gyroid (I4 1 32) photonic crystals. We describe their optical function from SAXS data and photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
412
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 454 publications
(429 citation statements)
references
References 47 publications
(96 reference statements)
10
412
1
Order By: Relevance
“…10-15 mm 3 but vary with taxon [49]). The azimuthally averaged scattering profiles were calculated from the CCD-collected two-dimensional SAXS speckle diffraction patterns using the freely available Matlabimplemented software, XPCSGUI, developed by beamline 8-ID (http://8id.xor.aps.anl.gov/UserInfo/Analysis/) at 200 equal q-partitions, and with customized masks to filter out the beam stop [15,38,50]. SAXS data from the feathers of Cittura cyanotis and the yellow throat of Psarisomus dalhousiae (see electronic supplementary material, tables S1 and S2) were collected using a 7.35 keV beam (1.68 Å , 50 mm horizontal  50 mm vertical, 9.24 m camera length, 50  0.1 s exposures) on a Pilatus2M detector at beamline I22 of the Diamond Light Source, Didcot, UK.…”
Section: Small Angle X-ray Scatteringmentioning
confidence: 99%
“…10-15 mm 3 but vary with taxon [49]). The azimuthally averaged scattering profiles were calculated from the CCD-collected two-dimensional SAXS speckle diffraction patterns using the freely available Matlabimplemented software, XPCSGUI, developed by beamline 8-ID (http://8id.xor.aps.anl.gov/UserInfo/Analysis/) at 200 equal q-partitions, and with customized masks to filter out the beam stop [15,38,50]. SAXS data from the feathers of Cittura cyanotis and the yellow throat of Psarisomus dalhousiae (see electronic supplementary material, tables S1 and S2) were collected using a 7.35 keV beam (1.68 Å , 50 mm horizontal  50 mm vertical, 9.24 m camera length, 50  0.1 s exposures) on a Pilatus2M detector at beamline I22 of the Diamond Light Source, Didcot, UK.…”
Section: Small Angle X-ray Scatteringmentioning
confidence: 99%
“…For example, pigmentation in flies, bees, and wasps is attributed to the presence of aromatic compounds heavily involved in cross-linking of the extracellular matrix, as well as to the occurrence of melanin in black-colored cuticle [35]. In the case of moth and butterfly wings, electron microscopy has revealed that cuticular structures are arrayed in multilayers or contain photonic crystals [36], both of which produce optical interference and can contribute to iridescent coloring.…”
Section: Optical Properties Of Fly Cuticlementioning
confidence: 99%
“…For example, gyroid and related phases have been reported recently [91,92]. Galusha et al have grown diamond-structured 3D photonic crystals by replicating the beetle shell using the sol-gel technique [93].…”
Section: Discussionmentioning
confidence: 99%